Presentation - Editors (Farol, 2024)
Issue 31 of Farol magazine brings together a collection of articles that explore the intersection between art, society and cultural practices in the contemporary context. The texts present critical and thought-provoking analyses that challenge our views on memory, subjectivity and social transformation, with a special focus on urgent issues in the Anthropocene.